2017
DOI: 10.3390/su9050727
|View full text |Cite
|
Sign up to set email alerts
|

Examining PM2.5 Emissions Embodied in China’s Supply Chain Using a Multiregional Input-Output Analysis

Abstract: Abstract:Haze has become an urgent problem for China's highly populated cities. Regional collaboration is an effective method for controlling air pollution. Because air pollution diffuses freely, it is necessary to distribute the responsibility for pollution with a common and differentiated rule. Based on a multiregional input-output model, this article calculated the PM 2.5 emissions embodied in provincial trade (EEPT) of China's 30 provinces in 2007 and 2010. The results show that the PM 2.5 EEPT accounts fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The industry-specific effects were positive or negative depending on the volume of particulate matter emission. Similarly, Wu et al [ 14 ] calculated the change in PM 2.5 emissions resulting from trade across provinces, and concluded that more than 30% of particulate matter was caused by multiregional economic activities. Wu et al [ 14 ] concluded that the Chinese government needs to establish different air pollutant mitigating policies that consider heterogeneous needs across stakeholders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The industry-specific effects were positive or negative depending on the volume of particulate matter emission. Similarly, Wu et al [ 14 ] calculated the change in PM 2.5 emissions resulting from trade across provinces, and concluded that more than 30% of particulate matter was caused by multiregional economic activities. Wu et al [ 14 ] concluded that the Chinese government needs to establish different air pollutant mitigating policies that consider heterogeneous needs across stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Wu et al [ 14 ] calculated the change in PM 2.5 emissions resulting from trade across provinces, and concluded that more than 30% of particulate matter was caused by multiregional economic activities. Wu et al [ 14 ] concluded that the Chinese government needs to establish different air pollutant mitigating policies that consider heterogeneous needs across stakeholders. Korea has a similar desire to reduce air pollutants, including PM 2.5 , due to its rapid economic growth fueled by a dramatic increase in energy consumption [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have carried out a large number of studies on PM 2.5 pollution in recent years. The research has mainly focused on the transboundary diffusion of PM 2.5 [14][15][16], the health effects of PM 2.5 [17][18][19][20], source analysis of PM 2.5 pollutants [21][22][23][24], simulation of PM 2.5 concentration [25][26][27][28], spatiotemporal changes and patterns of PM 2.5 pollution [29][30][31], contributing factors analysis of PM 2.5 concentration [32][33][34][35], establishing a PM 2.5 emissions inventory [36,37], and determining the dispersion of PM [38][39][40]. Total pollutant discharge control is a measure for environmental management, so reducing PM 2.5 emissions will be a commendable means of preventing PM 2.5 pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual CO 2 and pollutants embodied in trade or consumption have attracted much attention in the recent literature [2][3][4][5][6]. Studies concerning the determinants of China's CO 2 emissions growth have used various approaches and databases, among which Structural Decomposition Analysis (or SDA), based on input-output tables, has been frequently used [7][8][9].…”
Section: Introductionmentioning
confidence: 99%